Improvement of Facial Paralysis after Parotidectomy with Integrated Korean Medicine Treatment: A Case Report - Choong Hyun Han; Young Han Nam; Young Kyung Kim; Youn Young Choi; Eun Sol Won; Hwa Yeon Ryu; Jae Hui Kang; Hyun Lee (MEDrang Inc., 2024)
This study presents a case of facial nerve injury that occurred after parotidectomy for a benign tumor of the parotid gland that improved with integrated Korean medicine (IKM). On June 24, 2023, the patient presented with facial nerve injury based on a facial nerve conduction study after parotidectomy, with a score of five on Yanagihara's unweighted grading system (Y-system) and a grade of five on the House-Brackmann facial grading scale (H-B scale). During the 15 days of admission, IKM treatments, including acupuncture, pharmacopuncture, moxibustion, herbal steam therapy, physiotherapy, herbal medicine, and thread embedding acupuncture treatment, were performed. After treatment, the strength of the orbicularis oculi, orbicularis oris, and masticatory muscles improved, with a Y-system score of 17 and an H-B scale of III. In conclusion, the findings of this study confirm the applicability and effectiveness of IKM in the treatment of facial paralysis following parotidectomy.